The pro-apoptotic effect of a Terpene-rich Annona cherimola leaf extract on leukemic cell lines - Carl Ammoury; Maria Younes; Marianne El Khoury; Mohammad H. Hodroj; Tony Haykal; Peter Nasr; Marilyne Sily; Robin I. Taleb; Rita Sarkis; Rana Khalife; Sandra Rizk (BMC, 2019)
Abstract Background The edible fruit Annona cherimola has previously shown many nutritional and medicinal properties. The current study evaluates the anti-cancer and anti-proliferative properties of Annona cherimola ethanolic leaf extract (AELE) on Acute Myeloid Leukemia (AML) cell lines cultured in vitro (Monomac-1 and KG-1). Methods The anti-proliferative effect of A. cherimola ethanolic leaf extract was evaluated via cell viability assay. Its pro-apoptotic effect was assessed through Cell Death ELISA and dual Annexin V/PI staining. To further investigate the molecular mechanism by which the extract promoted apoptosis and inhibited the proliferation of the AML cells used, apoptotic protein expression was determined through western blots. Extract composition was elucidated by Gas Chromatography-Mass Spectrometry (GC-MS). Results Our results showed that the treatment with A. cherimola ethanolic leaf extract exhibited an inhibitory effect on the proliferation of both cancer cell lines used in a dose- and time-dependent manner, with no toxic effects on normal mononuclear cells (MNCs) isolated from human bone marrow. This effect was mediated by DNA fragmentation and apoptosis, as revealed by Cell Death ELISA and dual Annexin V/PI staining. Western blot analysis revealed a Bax/Bcl2 dependent mechanism of apoptosis, as well as PARP cleavage, confirming the apoptotic results observed previously. These effects may be attributed to the presence of terpenes which constitute a large component of the leafy extract, as revealed via GC-MS. Conclusion All the data presented in our study show that the terpene-rich A. cherimola ethanolic leaf extract exhibits an anti-proliferative and pro-apoptotic effect on the AML cell lines used.